Avaliação conjuntural da formação e do mercado de trabalho de engenheiros e engenheiras no Brasil - Ruas, André de Melo (Universidade Federal de São Carlos, 2023)
In Brazil, not all Engineering graduates work in careers typical of their area of study. Each year, the number of vacancies in Engineering schools increases, meanwhile Brazil experiences de-industrialization in recent decades, with a slower offer curve of vacancies in the labor market. The present work seeks to understand the reasons that lead engineers not to work with Engineering in Brazil, with a generalist look, passing through the Brazilian industrial scenario, the remuneration in different careers, the teaching method in Brazilian universities, the sociodemographic context of students and professors and, finally, personality and learning styles of Engineering students. This understanding is important so that it is possible to outline action plans to retain these brains in Brazil and in their typical expertise areas. The conflict of personality and learning styles with the prevailing method of teaching today, higher remuneration in financial services careers, gender disparities and the Brazilian deindustrialization of recent years, together, may explain the difficulty in retaining engineers in typical Engineering careers in Brazil.
Conjunctural evaluation of education and job market for engineers in Brazil
Keywords: Formação; Educação; Indústria; Evasão; Personalidade; ENGENHARIAS::ENGENHARIA MECANICA